Screening constant by unit nuclear charge method : description and application to the photoionization of atomic systems - Sakho, Ibrahima (John Wiley and Sons, Inc. ; ISTE, 2018)
The reader will find in this collection a clear exposition of the method of the Screen Constant by Nuclear Charge Unit which can be applied in a simple and immediate way to many fields of Physics in relation to atomic spectroscopy.